Horse impoundments under Control of Horses legislation in the Munster region of Ireland: factors affecting euthanasia. (24th January 2015) - Cullinane, M.; O'Sullivan, E.; Collins, D. M.; Byrne, A. W.; More, S. J.
Abstract : Recently, considerable international attention has been paid to the problem of unwanted horses. In Ireland, stray horses, particularly in urban areas, are a further problem. The Control of Horses Act 1996 was enacted in response to an ongoing problem of uncontrolled horses in public places. As yet, no research work has been conducted focusing on stray horses in Ireland. This paper describes horses impounded under the Act in the Munster region of Ireland during 2005–2012 and the factors influencing decisions regarding their disposal. A logistic regression model was developed to investigate factors influencing the probability that a horse was euthanised during impoundment. In total, 3625 seizure events were recorded, most towards the end of the study period. Predictors for euthanasia during 2010–2012 included seizure location, sex, age, colour, body condition score and year. This study highlights the problem of stray horses in Ireland, particularly in urban areas. There is a need for rigorous enforcement of newly enacted horse identification legislation, allowing a fully integrated traceability system. More is required to manage the long‐established societal problems of stray horses in urban settings, with a uniform approach by all Local Authorities being long overdue.